Factors influencing urban farmers’ intention to adapt to climate change in Addis Ababa, Ethiopia: a protection motivation theory - Getu, Endalkachew; Ayenew, Bereket; Singh, Kanchan; Worku, Mitiku Adisu (Frontiers in Climate, 2025)
Globally, climate change (CC) is a widely recognized fact, particularly in the past few decades. Developing nations like Ethiopia have been experiencing climate change and its effects on agriculture. In this regard, urban agriculture is one of the sectors significantly impacted by adverse change in climate. However, there is scant empirical evidence on the factors influencing urban farmers’ intention to adapt to climate change in urban centers of Ethiopia. To fill the research gap, this study aimed to identify factors influencing urban farmers’ intention to adapt to climate change in Addis Ababa, Ethiopia. In doing so, a quantitative research approach with a random sampling technique was applied. Based on the protection motivation theory (PMT), primary data were collected from 364 respondents using a survey questionnaire. Accordingly, structural equation modeling (SEM) was used to identify and analyze the underlying relationships among the nine constructs used in this study. Hence, the results revealed that selecting new crop varieties, water management practices, adjusting dates of sowing crops with changing local climatic conditions, and sowing drought-resistant crops were major adaptation practices. Hence, the perception of CC indicators, the perceived effects of CC, incentives, subjective norms, adaptation efficacy, and self-efficacy were found to positively and significantly influence urban farmers’ intention to adapt. In contrast, urban farmers (UFs) show less intention to adapt to CC when subjected to maladaptive behaviors. Based on this, the study recommends strengthening the capacity of local institutions, farmer training and education, climate information dissemination such as early warning systems, access to extension services, and access to finance to equip urban farmers to undertake practical adaptation strategies in the face of climate change.